THE NAGORNO-KARABAKH CONFLICT IN THE CONTEXT OF RETROSPECTIVE ETHNO-GEOPOLITICS - ALLAHVERDIEV, Kenan (CENTRAL ASIA AND THE CAUCASUS, 2009)
Why Karabakh? Why has this small patch of land been a bone of contention in the Caucasus for so long (since the 19th century)? The answers, not infrequently placed in political and ethnic contexts, are numerous: Historical memory of the various Caucasian nationalities about alleged ethnic insults; Antagonistic ethnopolitical contradictions due to the absence of ethnic complementariness among the main local ethnic groups; The clash between two major postulates of international law: the territorial integrity of states and the right of nations to self-determinationTerritorial claims that develop into aggression The geopolitically conditioned continuous conflict caused by the neo-imperial intentions of the main players on the world political scene;The opposing interests of the ethnic elites and clans that started the conflict in the first place to gain their own political and economic advantages, etc.The list is much longer than that, but the questions and answers should not be taken for abstract theorizing; an adequate description of the nature and genesis of the Karabakh conflict affects, in the most direct way, whether it can be resolved at all. Everything that politicians and academics have said so far about the conflict can be reduced to several paradigms: historical, civilizational, ethnopolitical, and geopolitical.Since the first three have been extensively covered in the academic literature, I selected the geopolitical context of the Nagorno-Karabakh conflict as the centerpiece of the present article. This analysis should not: First, be limited to the recent events and concentrate on the geopolitical collisions among the actors of current international politics;Second, be described in the terms of classical geopolitics (the regional context calls for internal and applied geopolitics);Third, ignore the ethnic (ethnopolitical) element invariably present in the seats of geopolitical tension of the so-called discontinuous belt of the Eurasian continent (to which the Caucasus belongs).This explains why my analysis of the Nagorno-Karabakh conflict concentrates on retrospective ethnic geopolitics. It is no great exaggeration to say that in the late 20th century the triad of geopolitics, ethnopolitics, and security served as the cornerstone of the most important approaches of political science to the world political processes unfolding before our eyes. Each of the categories taken separately looks at the highly varied and wide scope of the world political process through the prism of its dominant paradigm. Early in the 21st century the gap between the fairly complicated reality of international politics still in the process of formation and its basically mono-dimensional scholarly interpretation became too wide to be further ignored. This jolted the academic and political communities into the realization that they needed new, interdisciplinary approaches. The geopolitics/security combination and the varied interpretations of these terms have been extensively studied while many other possible combinations of the concepts described above have escaped equally close academic attention.The above explains why the present author has already substantiated the need to bring a new poly-paradigmatic category—ethnopolitical security— into academic circulation to be used in relevant research programs.1 Its usefulness, however, is of a limited nature: the paradigm related to the correlation between ethnopolitical factors and processes and the degree to which the vitally important interests of the key security entities are protected is necessarily limited to the present. The paradigm reaches its potential if the development trends in the sphere of ethnopolitical security are prolonged— this can be described as the paradigm’s tremendous advantage. It is obvious, at the same time, that the paradigm leaves the genesis of these processes and their relation to the historical reality of any specific ethnic, territorial, or political expanse outside the framework of study.This suggests a combination of two categories—ethnopolitics and geopolitics. In the 19th century, Friedrich Ratzel, the founding father of classical geopolitics, offered one of his key theses in his Political Geography, which so far has not been comprehensively understood. He wrote that the state emerged as an organism tied to a certain strip of land while its characteristics develop from the Volk (people) and the soil.2 The one-sided geopolitical approach betrayed itself in pushing aside Ratzel’s characteristics of the Volk for the sake of possible connections between politics and geographical factors.